2019
DOI: 10.21037/jtd.2018.12.43
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and prognostic value of B-type natriuretic peptide in left ventricular assist device recipients

Abstract: Background: The prognostic utility of B-type natriuretic peptide (BNP) in heart failure is well recognized. Previous studies demonstrated that BNP levels decrease after left ventricular assist device (LVAD) implantation. We sought to investigate the predictive value of baseline and changes in BNP levels in LVAD recipients. Methods: BNP was measured in baseline and follow-up plasma samples from consecutive patients receiving a continuous-flow LVAD from 2010 through 2016. Absolute values and changes from baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Five studies analyzed the predictive value of NPs for all-cause mortality, of which 4 studies included BNP and 1 study included NT-proBNP ( Table 2 ). None of the studies found BNP levels before LVAD implantation predictive of all-cause mortality ( 28 31 ). In contrast, NT-proBNP levels before LVAD implantation were predictive of 30-days all-cause mortality ( 32 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Five studies analyzed the predictive value of NPs for all-cause mortality, of which 4 studies included BNP and 1 study included NT-proBNP ( Table 2 ). None of the studies found BNP levels before LVAD implantation predictive of all-cause mortality ( 28 31 ). In contrast, NT-proBNP levels before LVAD implantation were predictive of 30-days all-cause mortality ( 32 ).…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, Topilsky et al demonstrated that preoperative NT-proBNP levels are predictive of 1-month mortality after LVAD implantation ( 32 ). The study by Papathanasiou et al analyzing BNP, had a similar study sample size and baseline characteristics compared to the study by Topilsky et al, but did not report a significant predictive relation ( 28 ). The differences in type of NPs and length of follow-up may have contributed to this contradictory finding.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They found no association between preimplant BNP concentrations, outpatient BNP at 3 months, and intra-individual change in BNP with all-cause mortality or hospitalization from any cause at 180 days. 24 One crucial difference from previous studies is that we have only utilized post-implant NT-pro BNP values obtained in ambulatory setting to characterize prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The early decrease in BNP level is indicative of ventricular unloading during ECLS but the rebound in BNP level after decannulation suggests BNP is not an ideal biomarker to predict complete normalization of cardiac function [ 5 ]. Other heart failure related biomarkers which have been explored in patients who underwent ECLS include dynamic BNP [ 8 ], galectin-3 [ 9 ], ST2 [ 10 ], matrix metalloproteinase-9 (MMP-9) [ 11 ], tissue inhibitors of metalloproteinase-1 (TIMP-1) [ 11 ], MMP-2 [ 11 , 12 ], osteopontin [ 13 ], MR-proANP [ 14 ], proADM [ 14 ], and copeptin [ 14 ]. The above-depicted biomarkers may assist to predict outcomes of heart failure requiring ECLS under limited circumstances and their identifications are summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%